Избранное - Дементьев Андрей Дмитриевич (Золотая серия поэзии, 2016)
Экземпляры: ф.23 (20241111) / Инвентарный номер: 65358 / Цена: / Сис.шифр: 84(2Рос=Рус)6-5 / Авт.знак: Д 30 / ГРНТИ: 17.82.10 / ББК: 84(2Рос=Рус)6-5